Noble motives, unjustified reasoning: a comment on allegations of genocide under the convention on the prevention and punishment of the crime of genocide (Ukraine v. Russian Federation) - Cao, Y (Foundation for Law and International Affairs, 2022)
The International Court of Justice recently delivered its Provisional Measures Order on the Ukrainian Genocide case, demanding an immediate suspension of the Russian military operation against Ukraine. This article examines three legal issues deriving from this order. Firstly, it evaluates the establishment of the ICJ’s prima facie jurisdiction under the compromissory clause of the Convention on the Prevention and Punishment of the Crime of Genocide. It finds that the Order inexplicably departed from the ICJ’s jurisprudence in the Legality of Use of Force cases, and that the existence of indispensable external jus ad bellum issues in the present case should have deprived the ICJ of its jurisdiction. Secondly, it assesses the plausibility of the rights sought, and finds that there is no plausible right under the Convention on the Prevention and Punishment of the Crime of Genocide to be free from military attacks based on a claim of preventing and punishing, since the parties could not have intended so. Thirdly, it analyzes the link between the claimed rights and the provisional measure granted and finds that this requirement is not satisfied in this case because the provisional measure indicated will also protect a right under jus ad bellum, which falls outside the ICJ’s jurisdiction. In view of the above, this article argues that although the Order might achieve the political objective of mitigating the conflict, the ICJ’s reasoning has been unconvincing or at least incomplete in legal terms, which risks undermining the ICJ’s reputation and reliability as well as the coherence and credibility of international law.